Human caring for the elderly in the community to promote healthy aging - Guerrero Castañeda, Raúl Fernando (2023)
The aging process is a vital process in which changes occur that challenge the adaptive process of the person without this being considered pathological. Promoting health in old age involves the need for a person-centered vision that goes beyond the limits of geriatric syndromes or the stereotyped decline of the older adult. The present essay aims to build a perspective of humanized care for the elderly in the community in order to favor healthy aging. Nursing care as a relationship that allows understanding the experience of health and well-being in the elderly is what is required to intervene with a closer approach and whose purpose is to incorporate nursing interventions that promote health care awareness in the elderly. These interventions should be considered from a creative and artistic vision of care, because they seek to promote an active and healthy aging, considering as a scenario the community environments as they constitute an area of opportunity for the nurse in the search for this sense of human care towards aging.